Protecting All Children's Teeth (PACT): Caries - Melinda Clark; David Krol (Association of American Medical Colleges, 2013)
Abstract This resource is a PowerPoint module that explains the process of caries, which, if untreated, can progress to a cavity. As dental caries is the most common chronic disease of childhood and disproportionately affects poor and minority populations, it is important for medical providers to prevent, identify, and appropriately triage caries. Educators can download the module for presentation in a didactic lecture/discussion format or assign learners to study it on their own. This resource is a part of Protecting All Children's Teeth (PACT), a series created by the American Academy of Pediatrics Oral Health Initiative to educate medical students, residents, pediatric primary care providers, and others interested in infant, child, and adolescent health about the importance of oral health in overall health. The curriculum provides in-depth coverage of child oral health, oral health guidance, and preventive care to increase comfort in recognizing dental disease and conditions and in communicating with dental professionals. PACT has been used since 2007 by physicians in training at various medical schools and residency levels, as well as by those in clinical practice.